Living Quran and Feminism: Changing Perceptions of Women's Careers in Contemporary Society - Dinda Febrianti Putri; Luthviyah Romziana; Himami Firdausi; Ahmad Fawaid (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The increasing participation of women in professional careers in religious communities has given rise to new dynamics in family relations and social perceptions based on religious values. This study aims to analyze the construction of meaning for women pursuing careers through the perspectives of the Living Qur'an and Islamic feminism, as well as the transformation of social acceptance in the Kraksaan community, Probolinggo. Using a case study approach, the study involved 23 career women informants from various professions selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña model and tested for validity through triangulation and member checking. The results show that internalization of Qur'anic values not only serves as a spiritual foundation but also as a social legitimacy for women's identities as professional breadwinners. In addition, the concept of religious professionalism emerged, namely the combination of competitive public performance and adherence to family values, resulting in a balanced role without triggering domestic or social conflict. This study contributes to the expansion of the Living Qur'an discourse by proposing a spiritual career feminism framework as a new paradigm in viewing the agency of modern Muslim women.